Time-Dependent Changes in Microglia Transcriptional Networks Following Traumatic Brain Injury - Izzy, Saef; Liu, Qiong; Fang, Zhou; Lule, Sevda; Wu, Limin; Chung, Joon Yong; Sarro-Schwartz, Aliyah; Brown-Whalen, Alexander; Perner, Caroline; Hickman, Suzanne E.; Kaplan, David L.; Patsopoulos, Nikolaos A.; et al. (Frontiers in Cellular Neuroscience, 2019)
The neuroinflammatory response to Traumatic brain injury (TBI) is critical to both neurotoxicity and neuroprotection and has been proposed as a potentially modifiable driver of secondary injury in animal and human studies. Attempts to broadly target immune activation have been unsuccessful in improving outcomes, in part because the precise cellular and molecular mechanisms driving injury and outcome at acute, subacute and chronic time points after TBI remain poorly defined. Microglia play a critical role in neuroinflammation and their persistent activation may contribute to long-term functional deficits. Activated microglia are characterized by morphological transformation and transcriptomic changes associated with specific inflammatory states. We analyzed the temporal course of changes in inflammatory genes of microglia isolated from injured brains at 2, 14 and 60 days after controlled cortical impact in mice, a well-established model of focal cerebral contusion. We identified a time dependent, injury-associated change in the microglial gene expression profile toward a reduced ability to sense tissue damage, perform housekeeping, and maintain homeostasis in the early stages following injury, with recovery and transition to a specialized inflammatory state over time. This later state starts at 14 days post injury and is characterized by a biphasic pattern of IFNγ, IL-4 and IL-10 gene expression changes, with concurrent proinflammatory and anti-inflammatory gene changes. Our transcriptomic data sets are an important step to understand microglial role in TBI pathogenesis at the molecular level and identify common pathways that affect outcome. More studies to evaluate gene expression at the single cell level and focusing on subacute and chronic timepoint are warranted.